2014
DOI: 10.1007/s11248-014-9839-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant characterization of Roundup Ready 2 Yield® soybean, MON 89788, for use in ecological risk assessment

Abstract: During the development of a genetically modified (GM) crop product, extensive phenotypic and agronomic data are collected to characterize the plant in comparison to a conventional control with a similar genetic background. The data are evaluated for potential differences resulting from the genetic modification process or the GM trait, and the differences--if any--are subsequently considered in the context of contributing to the pest potential of the GM crop. Ultimately, these study results and those of other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 13 publications
2
26
1
Order By: Relevance
“…15 For MON 89788 there were no or few differences detected across the germination, phenotypic, and pollen studies that would increase the weediness and invasive characteristics of MON 89788, so the hazard for these particular endpoints would be negligible. 10 Based on a tiered assessment approach, the germination, emergence and plant growth, and reproduction data presented in Horak et al 10 did not indicate any differences that would indicate the need for further assessments of weediness and invasiveness. However, in order to address specific regulatory requirements and the other needs described above, the studies reported herein were conducted.…”
Section: Hazard Characterization and Data Transportabilitymentioning
confidence: 95%
See 4 more Smart Citations
“…15 For MON 89788 there were no or few differences detected across the germination, phenotypic, and pollen studies that would increase the weediness and invasive characteristics of MON 89788, so the hazard for these particular endpoints would be negligible. 10 Based on a tiered assessment approach, the germination, emergence and plant growth, and reproduction data presented in Horak et al 10 did not indicate any differences that would indicate the need for further assessments of weediness and invasiveness. However, in order to address specific regulatory requirements and the other needs described above, the studies reported herein were conducted.…”
Section: Hazard Characterization and Data Transportabilitymentioning
confidence: 95%
“…The studies reported in Horak et al 10 Protocol 12 or other publications. 6,7 However, from a practical standpoint, these characterization studies provide regulators with information that is either required by government authorities or assists in decision making by addressing perceived uncertainty.…”
Section: Hazard Characterization and Data Transportabilitymentioning
confidence: 99%
See 3 more Smart Citations